Characterization of Synthesized Heterocyclic Oxadiazole Derivatives Using Mass, UV, IR, and NMR Spectroscopy, Among other Spectroscopic Techniques: Review - Rizwan Arif; Neha Sahu (International Journal of Photochemistry and Photochemical Research, 2024)
The current study synthesized and assessed 3-heteroarylazo 4-hydroxy coumarin derivatives' initial antibacterial activities in vitro against four distinct pathogenic bacterial strains, including Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli, and Staphylococcus aureus. Ampicillin, a common medication, was used to compare each compound's antibacterial properties. UV, IR, 1H NMR, mass spectroscopy, and X-ray diffraction examinations were used to analyze the compounds. By using UV–vis spectra, the solute-chromic behavior of these compounds was also examined. Every product demonstrated increased antibacterial potential against every bacterial strain, with the exception of 4g, as demonstrated by the zone of inhibition and lowest inhibitory concentration. While pyrazolone azo analogue 4e has strong antibacterial activity, 3-Thiazolylazo and 3-(4-phenyl thiazolylazo) of 4-hydroxy coumarin have demonstrated a good zone of inhibition against both gram +ve and gram −ve germs. In order to determine the structures of the recently synthesized derivatives, mass spectrometry, 1H NMR, IR, UV, and 1C NMR were all used together. In addition, these synthetic compounds were tested for antibacterial efficacy against all of the chosen microbial strains in contrast to cefixime and amoxicillin. The aim was to evaluate the derivatives' potential as peptide deformylase inhibitors with respect to antibacterial activity. Using p-hydroxy benzaldehyde and phenyl hydrazine, a novel series of physiologically active triazole and pyrazole compounds containing 2, 4-disubstituted thiazole analogues were produced in outstanding yields and purity. Based on their spectrum data studies (IR, 1H-NMR, 13C-NMR spectra, and HRMS), all of the synthesized substances were definitively identified. After careful purification, the final derivatives were assessed for their in vitro anti-microbial activity.
Keywords: 4-Oxadiazole derivatives; Antibacterial; anticandidal activity; antifungal agents; antioxidant; molecular docking